Komunikasi Partisipasi Masyarakat dalam Musrenbang sebagai Instrumen Demokrasi Perencanaan Pembangunan di Kecamatan Siantar Martoba - Fajrina, Raidhaul; Humaizi, Humaizi; Warijo, Warijo (Mahesa Research Center, 2025)
National development requires systematic and participatory planning, as mandated by Law No. 25 of 2004 on the National Development Planning System. The Development Planning Deliberation Forum (Musrenbang) is designed to integrate community aspirations with local government agendas. However, in Siantar Martoba District its implementation still faces challenges, including weak socialization, government dominance, and limited representation of marginalized groups. This study examines communication in community participation during the 2025 Musrenbang. Using a qualitative descriptive approach, data were gathered through in-depth interviews, participatory observation, and documentation involving six key informants from local government, community leaders, and active participants. The results indicate that although Musrenbang is procedurally aligned with regulations, communication remains one-way, technocratic language hinders public understanding, and many community proposals are not realized in planning documents or development programs. The study concludes that Musrenbang functions more administratively than deliberatively, highlighting the need for more inclusive, transparent, and community-based communication strategies to strengthen participation in local development.